Analisis Faktor-faktor yang Berpengagruh Terhadap Keputusan Nasabah Memilih Bank Syariah - Lia Apri Yanti (ITB AAS INDONESIA Surakarta, 2021)
ANALYSIS OF FACTORS AFFECTING A CUSTOMER DECISION TO CHOOSE A SHARIA BANK Abstract The market share of Islamic banks in Indonesia is still below 6% of the national banking market share, in stark contrast to the number of Indonesians who are predominantly Muslim. The purpose of this study is to prove what factors influence customers in choosing Islamic banks. Research variables consist of Knowledge, Product Quality, Promotion, Motivation, Attitude and Religion as independent variables while the dependent variable is the customer's decision to choose a Sharia bank. The object of this research is the customers of Islamic banks in the Greater Jakarta area, with 130 respondents as sample. Quantitative data analysis using Amos software version 23. The results prove that the Knowledge variable has a significant effect on customer decisions in choosing Islamic banks. Product Quality Variable has a significant effect on customer decisions in choosing Islamic banks. Promotion variables have a significant effect on customer decisions in choosing Islamic banks. Motivation variables have a significant effect on customer decisions in choosing Islamic banks. Religious variables have a significant effect on customer decisions in choosing Islamic banks, while Attitude variables have no significant effect on customers in choosing Islamic banks. Keywords: Knowledge, Product Quality, Promotion, Motivation, Attitude, Religious and :Decision